Women of Faith : The Chicago Sisters of Mercy and the Evolution of a Religious Community - Connolly, Mary Beth Fraser (Book collections on Project MUSE., 2014)
When the Sisters of Mercy lost their foundress Sister Catherine McAuley in 1841, stories of Mother Catherine passed from one generation of sisters to the next. McAuley's Rule and Constitutions along with her spiritual writings and correspondence communicated the Mercys' founding charism. Each generation of Sisters of Mercy who succeeded her took these words and her spirit with them as they established new communities or foundations across the United States and around the world. In Women of Faith, Mary Beth Fraser Connolly traces the paths of the women who dedicated their lives to the Sisters o.